Empowering the NSC-34 cell line as a motor neuron model: Cytosine arabinoside’s action - Giuseppe Vitale; Susanna Amadio; Francesco Liguori; Cinzia Volonté (Neural Regeneration Research)
The NSC-34 cell line is a widely recognized motor neuron model and various neuronal differentiation protocols have been exploited. Under previously reported experimental conditions, only part of the cells resemble differentiated neurons; however, they do not exhibit extensive and time-prolonged neuritogenesis, and maintain their duplication capacity in culture. The aim of the present work was to facilitate long-term and more homogeneous neuronal differentiation in motor neuron–like NSC-34 cells. We found that the antimitotic drug cytosine arabinoside promoted robust and persistent neuronal differentiation in the entire cell population. Long and interconnecting neuronal processes with abundant growth cones were homogeneously induced and were durable for up to at least 6 weeks in culture. Moreover, cytosine arabinoside was permissive, dispensable, and mostly irreversible in priming NSC-34 cells for neurite initiation and regeneration after mechanical dislodgement. Finally, the expression of the cell proliferation antigen Ki67 was inhibited by cytosine arabinoside, whereas the expression levels of neuronal growth associated protein 43, vimentin, and motor neuron–specific p75, Islet2, homeobox 9 markers were upregulated, as confirmed by western blot and/or confocal immunofluorescence analysis. Overall, these findings support the use of NSC-34 cells as a motor neuron model for properly investigating neurodegenerative mechanisms and prospectively identifying neuroprotective strategies.